(untitled) (Journal of the College of Education for Women, 2019)
The resort to the eloquence of the poetic image as a style reveals the poet’s creativity and creativity in dealing with external influences, and reflect them with emotional images express a sense of intense emotional imagination, and this imagination stems from the experience of a poetic sense of truth, tasted by the recipient before the creator of the poetic text.